Communication Strategies For Islamic Businesses In Facing Competition In The Digital Age - Kartini (CV Putra Publisher, 2026)
Sharia business communication is becoming increasingly important as digital competition transforms the way businesses promote products, negotiate, serve customers, and build trust. This article analyses Sharia business communication strategies in the face of digital-era competition by synthesising the literature on Sharia communication in the digital transformation of SMEs and value-based Islamic organisational communication. The research employs a qualitative descriptive approach through a literature review and thematic analysis. The findings identify five pillars of strategy: honest and transparent product communication; digital trust based on amanah; internal coordination based on musyawarah; halal and ethical content branding; and transactional communication aligned with Sharia principles. Digital competition cannot be adequately addressed merely through mastery of platforms, algorithms, and promotional speed. Business operators must also demonstrate ethical discipline, clarity of contracts, data responsibility, fair pricing, and consistent after-sales service. A Sharia communication strategy can strengthen market differentiation, customer loyalty, team synergy, and business sustainability when implemented through communication operational standards, Sharia digital literacy, halal certification, and measurable communication indicators. This article offers a practical framework for SMEs and Islamic business organisations seeking to compete ethically in the digital marketplace